#### Answer

The solution of the system is $\underline{\left( 1,-3 \right)}$.

#### Work Step by Step

Let us consider the system of equations:
$ x=y+4$
$ x-y=4$ (I)
$3x+7y=-18$ (II)
And multiply the equation (I) with $-3$ and then obtain,
$-3x+3y=-12$ (III)
And add the equations (II) and (III) as given below:
$\begin{align}
& 3x+7y-3x+3y=-18-12 \\
& 7y+3y=-30 \\
& 10y=-30 \\
& y=-3
\end{align}$
Put the value of y in the equation (I), to compute the value of x.
$\begin{align}
& x-\left( -3 \right)=4 \\
& x+3=4 \\
& x=1
\end{align}$
Thus, the values are $ x=1$ and $ y=-3$.